High-throughput screening Raman microspectroscopy for assessment of drug-induced changes in diatom cells - Rueger, Jan; Mondol, Abdullah Saif; Schie, Iwan W.; Popp, Jürgen; Krafft, Christoph (Analyst, 2019)
High-throughput screening Raman spectroscopy (HTS-RS) with automated localization algorithms offers unsurpassed speed and sensitivity to investigate the effect of dithiothreitol on the diatom Phaedactylum tricornutum. The HTS-RS capability that was demonstrated for this model system can be transferred to unmet analytical applications such as kinetic in vivo studies of microalgal assemblages.
CRIS-Team Scopus Importer:2023-04-20